Homozygous CREM-IbΔC-X Overexpressing Mice Are a Reliable and Effective Disease Model for Atrial Fibrillation - Stümpel, Frank T.; Stein, Juliane; Himmler, Kirsten; Scholz, Beatrix; Seidl, Matthias D.; Skryabin, Boris V.; Müller, Frank U. (Frontiers in Pharmacology, 2018)
Background: Atrial fibrillation (AF) is a significant cause of morbidity and mortality with foreseeably increasing prevalence. While large animal models of the disease are well established but resource intensive, transgenic AF mouse models are not yet widely used to develop or validate novel therapeutics for AF. Hemizygous mice with a cardiomyocyte-specific overexpression of the human cAMP response element modulator (CREM) isoform IbΔC-X spontaneously develop AF on grounds of an arrhythmogenic substrate consisting of alterations in structure, conduction, and calcium handling. Objective: We investigated if homozygous expression of the CREM-IbΔC-X transgene in mice alters the time course of AF development, and if homozygous CREM-IbΔC-X transgenics could be suitable as a disease model of AF. Methods: Southern Blot, quantitative real-time PCR, and immunoblotting were used to identify and verify homozygous transgenics. Cardiac gravimetry, quantitative real-time RT-PCR, histology, survival analysis, and repeated ECG recordings allowed assessment of phenotypic development and effects of antiarrhythmic drugs. Results: Homozygous animals could be identified by Southern blot and quantitative PCR, showing a strong trend to increased transgenic protein expression. In homozygous animals, atrial hypertrophy appeared earlier and more pronounced than in hemizygous animals, going along with an earlier onset of spontaneous AF, while no increased early mortality was observed. Application of a rate-controlling drug (esmolol) led to the expected result of a decreased heart rate. Application of a rhythm-controlling drug (flecainide) showed effects on heart rate variability, but did not lead to a definitive conversion to sinus rhythm. Conclusion: We suggest homozygous CREM-IbΔC-X overexpressing mice as a reliable model of early onset, rapidly progressive AF.